Can Demand Forecasting Help Supply Chain? Evidence from Beer Distribution Game - Nengah Widiangga Gautama; Andi Harmoko Arifin (Return : Study of Management, Economic and Bussines, 2024)
One of complex process known nowadays which involves production, delivery and services to consumers is supply chain. Supply chain often can be simplified and analyzed with simulations like Beer Distribution Game. In this research, we use an extended version of Beer Distribution Game, built by AnyLogic, and equipped with additional feature such as information sharing. This research uses a simulation experiment method, and from the experiment’s result we draw a conclusion based on the effect of SMA forecasting. It is shown that by adding SMA forecasting only at the Retailer unit, does not conclusively reduce the BDG’s Total Cost